Глобальный город как продукт процесса глобализации - Воронин, И.Н. (Культура народов Причерноморья, 2013)
В статье анализируется влияние процессов глобализации на формирование нового
урбанистического явления – глобальных городов. Дана классификация глобальных городов и
характеристика основных городских систем. У статті аналізується вплив процесів глобалізації на формування нового урбаністичного
явища – глобальних міст. Дана класифікація глобальних міст і характеристика основних міських
систем. In the article analyzes the impact of globalization on the formation of a new urban phenomenon – the
global cities. Global city – it is the headquarters of the post-industrial economy, there are offices of international
organizations, major financial institutions, commodity and currency exchanges, the central offices of
multinational corporations and banks, the headquarters of the global media corporations and law firms,
financial and political associations, international non-governmental organization.
The authors “concept of global cities” are the American sociologists and economists S. Sassen- Koob and A.
King. In their view, global cities – are the centers of global economic governance, concentration of finance and
innovation. The problem of the formation of global cities also engaged P. Hall, M. Castles, D. Friedman, P.
Taylor. Is a synonym for “global city” – a World City, Metropolis, Ideapolis, Information City, Megapolis,
Megalopolis.
The first classification of world cities held American research company The Globalization and World Cities
(GaWC) in 1998 on the following criteria: the presence of the headquarters and offices 4 business services –
financial, accounting, advertising and legal. There are three classes of world cities: “α-alpha”, “β-beta” and
“γ-gamma”. Distinguishes 3 main habitats of world cities – Europe, the U.S. and the Asia-Pacific Region (APR),
which represent the city of all classes – α-, β- and γ-cities.
Currently in the world there are only three α-cities that are located in the geopolitical Center and compete with
each other. This is New York, London and Tokyo. The affected area of New York City – North and South
America, London – Europe, Africa, Middle East, South Asia and the former Soviet Union, respectively, East
Asia, Australia and Oceania are under the influence of Tokyo. On the Semi-Periphery is β-cities (Moscow, Sao
Paulo, Seoul), in the Periphery few γ-Cities